(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The doctor-nurse relationship plays a crucial role in healthcare delivery, yet it is often hindered by stereotypes and misconceptions. This article explores common biases such as gender stereotypes, hierarchical assumptions, and task-based misconceptions that impact collaboration between doctors and nurses. Strategies for overcoming these barriers include education and training, promoting open communication, challenging gender norms, establishing clear expectations, and celebrating success stories. By addressing stereotypes and misconceptions, doctors and nurses can foster a culture of mutual respect, improve teamwork, and ultimately enhance patient care outcomes.